Race, Gender, and Program Type as Predictive Risk Factors of Recidivism for Juvenile Offenders in Georgia - Matheson Sanchez; Gang Lee (Journal of Public and Professional Sociology)
Race, gender and program type have shown to be effective predictors of future recidivism for juveniles. Previous research shows that minority juveniles offend and recidivate at a higher rate than white juveniles do. Previous research also shows that male juveniles offend and recidivate at a higher rate than female juveniles do. Past literature shows that juveniles who receive rehabilitative sanctions are less likely to recidivate that juveniles who receive punitive punishment. The current study aims to test these relationships for juveniles in Georgia, USA, utilizing a department of juvenile justice archival dataset (N = 12,030). Bivariate and multivariate analyses are performed. Black juveniles and male youths were found to have higher levels of recidivism than white and female youths. Female juveniles were found to recidivate following a shorter period of time following release from custody. Juveniles who were given therapy-based treatment in lieu of traditional custodial sanctions were found to be at a lower risk of reoffending. Plausible causation and needs for future research are explored.